2016
DOI: 10.1002/pc.24133
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of nanocomposites made from chemoenzymatically prepared polyester urethanes and functionalized multiwalled carbon nanotubes

Abstract: Multiwalled carbon nanotubes (MWNTs) were functionalized with four different functional groups and used as nanofillers to reinforce biodegradable polyurethanes (PU), in an effort to explore their effect on the thermal and mechanical properties of the obtained nanocomposites. The PU were synthesized via one step process, by the reaction between a αω‐telechelic polyester diol (obtained by biocatalysis from ε‐caprolactone and diethylene glycol), and hexamethylene diisocyanate. The MWNTs were synthesized via a che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 54 publications
0
12
3
Order By: Relevance
“…On the contrary, for both types of nanocomposites, unidirectional tensile tests and TGA results show that CNTs f improves some of their mechanical properties (highlighting the toughness of nanocomposites prepared by two‐step method) and its thermal stability. Interfacial adhesion, thermal, and mechanical properties of the nanocomposites studied were a function of the amount of CNTs added, in contrast to the behavior observed for the nanocomposites studied in our previous report, where the effect of the amount of CNTs on these properties was not important . In general, mechanical properties of nanocomposites prepared by two‐step show better properties than those observed in nanocomposites prepared by one‐step.…”
Section: Discussioncontrasting
confidence: 87%
See 4 more Smart Citations
“…On the contrary, for both types of nanocomposites, unidirectional tensile tests and TGA results show that CNTs f improves some of their mechanical properties (highlighting the toughness of nanocomposites prepared by two‐step method) and its thermal stability. Interfacial adhesion, thermal, and mechanical properties of the nanocomposites studied were a function of the amount of CNTs added, in contrast to the behavior observed for the nanocomposites studied in our previous report, where the effect of the amount of CNTs on these properties was not important . In general, mechanical properties of nanocomposites prepared by two‐step show better properties than those observed in nanocomposites prepared by one‐step.…”
Section: Discussioncontrasting
confidence: 87%
“…On the other hand, for nanocomposites prepared by a two‐step approach, CNTs OH, COOH , CNTs et diam , or CNTs 4AB are also covalently attached to some PU chains, also via a chemical reaction where terminal isocyanate groups participated. In contrast, in our previous study on nanocomposites, it was not found evidence of formation of covalent bonds between the chemical groups of PU matrix and functionalized CNTs …”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations